A STRANGE DOUBLE EMPIRICAL TRANSCENDENTAL KANT, SLEEP ONSET ANTHROPOLOGICAL - OCAMPO SEPÚLVEDA, GABRIEL (Disertaciones, 2012)
The path of the present research paper has the purpose of recognise that the ontological/anthropological problem about us is far from having a plausible answer. So many back and forth around the same is a sign that the problem is still burning us, the matter is far from having reached a good explanation despite the words of the ones who profess a blind faith on science and modernity and argue that every problem, even the philosophical ones, can be solved with logic, numbers, technology and good management. Nonetheless, the paper does not tend to the opposite side, the irrationalism.